Framing the issues: Agriculture's Journey From Durban to Rio+ and beyond - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Speakers: - Mendes Ribeiro Filho, Minister of Agriculture, Livestock and Food Supply, Brazil - Rachel Kyte, World Bank Vice President for Sustainable Development and CGIAR Fund Council Chair Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday